2010
DOI: 10.1016/j.electacta.2009.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Carbon paste electrodes modified by Pt and Pt–Ni microparticles dispersed in polyindole film for electrocatalytic oxidation of methanol

Abstract: a b s t r a c tElectrocatalytic activity of the Pt microparticles dispersed into polyindole (PIn) films obtained by electropolymerization on carbon paste electrodes (CPE) towards methanol oxidation in perchloric acid medium has been demonstrated and investigated using cyclic voltammetry, potentiodynamic polarization, chronoamperometry and impedance spectroscopic techniques. The results show that PIn films obtained on these electrodes serve as good host matrices for the dispersion of Pt microparticles and exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 39 publications
0
16
1
Order By: Relevance
“…The mechanism of the promoting effect of Pt-Ni alloy is based on the synergistic roles of Pt and nickel hydroxides on the surface of the catalysts and the modification of the electronic characteristics of the surface Pt atoms by Ni atoms [8,9]. A considerable amount of research on Pt-Ni alloy catalyst in acid media is reported recently [9][10][11][12][13]. With the application for alkaline anion membrane in fuel cells [14,15], Pt-Ni alloy catalysts are potentially capable of being effectively employed in methanol oxidation.…”
Section: Introductionmentioning
confidence: 98%
“…The mechanism of the promoting effect of Pt-Ni alloy is based on the synergistic roles of Pt and nickel hydroxides on the surface of the catalysts and the modification of the electronic characteristics of the surface Pt atoms by Ni atoms [8,9]. A considerable amount of research on Pt-Ni alloy catalyst in acid media is reported recently [9][10][11][12][13]. With the application for alkaline anion membrane in fuel cells [14,15], Pt-Ni alloy catalysts are potentially capable of being effectively employed in methanol oxidation.…”
Section: Introductionmentioning
confidence: 98%
“…The electrocatalytic oxidation of small organic molecules, such as CH 3 OH, HCOOH, and HCHO, has been widely investigated for many years and continues to be of interest due to their potential utilization as fuels in fuel cells [14][15][16][17][18]. The reasons for that are related to their facility of storage and handling, and mainly their high energy density.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, scientists have paid attention to the applications of CPs as electrode materials in electrochromic devices (ECDs) because CPs are capable of changing their optical properties at various voltages [4]. CPs have been extensively used for several regions, such as solar cells [5,6], catalysts [7][8][9], polymer light-emitting diodes [10][11][12], supercapacitors [13,14], sensors [15,16], and ECDs [17,18].…”
Section: Introductionmentioning
confidence: 99%